ANALISIS PENGARUH PENDIDIKAN FORMAL, KESEHATAN PENDUDUK, PERDAGANGAN INTERNASIONAL, JUMLAH INVESTASI DAN DISTRIBUSI PENDAPATAN TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Mike Triani (Universitas Negeri Padang, 2014)
The purpose of this study was to determine and analyze The effect of formal education , international trade , the health of the population the amount of investment , and income distribution affects economic growth in provinces in Indonesia. The scope of this study is to analyze the variable distribution of income , economic growth in the provinces in Indonesia . It also uses a variable formal education , international trade , health , and investment . Based on the time it was collected , the data used in this study using the pooling of data ( panel data) period of 2008 to 2010.Keywords: formal education , international trade , the health of the population total investment and economic growth